On Bilingual Aptitude for Learning New Languages: The Roles of Linguistic and Nonlinguistic Individual Differences. Issue 2 (5th March 2019) - Cox, Jessica G.; Lynch, Julianna M.; Mendes, Najee; Zhai, ChengCheng
Abstract: An enduring question is whether language learning aptitude is a stable trait or is one influenced by experience, such as living with two languages. We investigated aptitude in bilinguals and treated their bilingual experience as an aggregate of variables, focusing on how individual differences in (a) language experience variables of proficiency, exposure, and age of onset and (b) nonverbal IQ explain variability in aptitude. Results from 80 Spanish–English bilinguals in the United States revealed positive relationships between balanced proficiency in Spanish and English, nonverbal IQ, and aptitude for grammatical inferencing. Similar relationships, plus a positive role for more exposure to bilinguals' more dominant language, emerged for aptitude in building sound–symbol associations. No aptitude component related to age of onset and age at testing, nor did any language experience variable or IQ relate to aptitude for sound recognition. We discuss results vis‐à‐vis language and cognition in minority language bilinguals. Abstract :